Problem konstytucyjności tzw. ustawy o bestiach: The constitutionality problem of the „act of beasts” - Krawczyk, Paweł (Management and Administration Journal, 2021)
The act voted in day 22 November 2013, about procedure concerning persons with mental disturbances who could threaten life, health or sexual freedom of other persons, many legal doubts wakes up. First of all, it is supposed that the act breaks constitutional principle of the legal state.